The national wealth tax on indigenous energy resources policy framework and implementation - Delfin, Francisco G., Jr (Philippine Journal of Public Administration, 2001)
Local governments' share of the national wealth tax on indigenous energy resource utilization, a program emanating from the 1991 Local Government Code, reached more than P2.0 billion during the period 1992-2001. Royalty from geothermal and hydropower resources accounted for 89 percent of the total, with taxes on local petroleum and coal production supplying the rest. Except for Region I and the National Capital Region, all of the country's administrative regions profited from the extraction of indigenous energy resources. Regions IV, V, and VII have the largest shares in royalty remittance, accounting for over half of the P2.0 billion fund. Although successful in generating revenues for local governments, several implementation problems prevent the policy from attaining its full potential. While most of the problems are related to bureaucratic processes that are now being addressed, it is argued that the most crucial - territorial disputes among local government units over ownership of energy resource - is presently difficult to resolve due to the basic technical underdevelopment of the Philippine administrative system.